Основні напрями соціально-економічного розвитку малих монофункціональних міст України - Доценко, А.І. (Український географічний журнал, 2011)
В статье дана характеристика состояния демографического, экономического и социального развития малых городов Украины, их экологического состояния. Выделены функциональные типы малых городов. Рекомендованы приоритетные направления экономического развития каждого из выделенных функциональных типов малых городов. The paper presents the characteristics of the state of the demographic, economic, social development and environmental conditions of small cities of Ukraine. The functional types of the small cities are defined. The priority directions of economic development of each of the defined functional types of Ukraine’s small cities are substantiated.